Diverse levels of sequence selectivity and catalytic efficiency of protein-tyrosine phosphatases. - Selner, N; Luechapanichkul, R; Chen, X; Neel, BG; Zhang, Z; Knapp, S; Bell, C; Pei, D (2014)
The sequence selectivity of 14 classical protein-tyrosine phosphatases (PTPs) (PTPRA, PTPRB, PTPRC, PTPRD, PTPRO, PTP1B, SHP-1, SHP-2, HePTP, PTP-PEST, TCPTP, PTPH1, PTPD1, and PTPD2) was systematically profiled by screening their catalytic domains against combinatorial peptide libraries. All of the PTPs exhibit similar preference for pY peptides rich in acidic amino acids and disfavor positively charged sequences but differ vastly in their degrees of preference/disfavor. Some PTPs (PTP-PEST, SHP-1, and SHP-2) are highly selective for acidic over basic (or neutral) peptides (by >10(5)-fold), whereas others (PTPRA and PTPRD) show no to little sequence selectivity. PTPs also have diverse intrinsic catalytic efficiencies (kcat/KM values against optimal substrates), which differ by >10(5)-fold due to different kcat and/or KM values. Moreover, PTPs show little positional preference for the acidic residues relative to the pY residue. Mutation of Arg47 of PTP1B, which is located near the pY-1 and pY-2 residues of a bound substrate, decreased the enzymatic activity by 3-18-fold toward all pY substrates containing acidic residues anywhere within the pY-6 to pY+5 region. Similarly, mutation of Arg24, which is situated near the C-terminus of a bound substrate, adversely affected the kinetic activity of all acidic substrates. A cocrystal structure of PTP1B bound with a nephrin pY(1193) peptide suggests that Arg24 engages in electrostatic interactions with acidic residues at the pY+1, pY+2, and likely other positions. These results suggest that long-range electrostatic interactions between positively charged residues near the PTP active site and acidic residues on pY substrates allow a PTP to bind acidic substrates with similar affinities, and the varying levels of preference for acidic sequences by different PTPs are likely caused by the different electrostatic potentials near their active sites. The implications of the varying sequence selectivity and intrinsic catalytic activities with respect to PTP in vivo substrate specificity and biological functions are discussed.